Early Postnatal Diet Differentially Affects the Fecal Microbiome and Metabolome (FS04-02-19). (13th June 2019) - Brink, Lauren; Chintapalli, Sree; Mercer, Kelly; Piccolo, Brian; Adams, Sean; Bowlin, Anne; Matazel, Katelin; Shankar, Kartik; Badger, Thomas; Andres, A; Yeruva, Laxmi
Abstract: Objectives: Infants who receive breastmilk have better immune response compared to formula fed children in part due to differences in their gut microbiome and metabolome. The aim of the study is to describe microbiota and metabolome differences and associations between these factors' in 3 and 12 month old infants who exclusively received breast milk (BM) or either soy (SF) or dairy (DF) formula until 4 months of age. Methods: Samples from 3 month old infants (BM = 10, DF = 8, SF = 9) and 12 month old infants (BM = 22, DF = 12, SF = 10) were obtained from infants fed formula or BM exclusively for 4 months. Fecal metabolomics and microbiota were assessed by LC-MS and 16s rRNA sequencing, respectively. Data analyses were conducted using standardized pipelines (QIIME 1.9, R, and Metabo-Analyst). Results: At 3 months of age, both the fecal microbiome and metabolites were affected by diet. The BM group had the lowest microbial diversity (Shannon index) and the SF had the highest diversity ( P  < 0.01) at genera taxonomic level while DF fell in the middle. There were 41 metabolites affected by diet at 3 months of age ( P  < 0.05, FDR < 0.05). Hippuric, succinic, lactic and uric acids were higher in the BM group and butyric and propionic acids were higher in the formula groups ( P  < 0.01). Correlation analyses revealed extensive associations within each diet type. For instance, we observed positive associations between succinic acid and Lactobacillus in BM group and lactic acid with Salmonella and Clostridium in SF group. Streptococcus and butyric acid in the DF, and Bifidobacterium and indole-2-carboxylic acid in the SF were negatively associated. At 12 months of age, there were no differences in microbial diversity and only fecal inosine remained significantly ( P  < 0.05) different among the diet groups. This metabolite was found to be negatively associated with Bifidobacterium in the breastfed group ( P  < 0.01). Conclusions: There is a strong effect of diet on the fecal metabolome and microbiota at 3 months of age. Additionally, multiple associations between the two across various diets are apparent, suggesting that differences in specific gut bacteria influence the metabolite milieu. Future mechanistic studies will examine the roles of microbiota and metabolites in immune function. Funding Sources: USDA-ARS Project 6251-51000-010-05S and NIH P20GM121293.